Pengembangan Sistem Informasi Data KB dan Analisis Pola Pemilihan Metode Kontrasepsi Menggunakan Algoritma Sql-Based Fp-Growth - Yumina Jumiati; Nurdin Bahtiar (Performa: Media Ilmiah Teknik Industri, 2015)
One of Unit Pelaksana Teknis Pemberdayaan Masyarakat, Perempuan, dan Keluarga Berencana (UPT BAPERMASPER dan KB) Region XV District of Mijen’s duty is to lead, plan, do, evaluate, and report the data management in service, management, and control of family planning programs and the empowerment of women in the district. The inadequate number offield officers (PLKB) often become spectacle in collecting and reporting the data KB. Family Planning Data Information System (SIDAK) is developed in order to support the mentioned task to make it easier to report, store, and manage the data. Additionally, SIDAK is equipped with a data analysis feature with association mining technique using SQL-Based FP-Growth algorithm. This algorithm analyze the data KB and create a relation (association rule) between the attributes used for analysis; the wive’s age, the highest education achieved by the couple, the number of children, the welfare level, and the contraception method. The research analysis of 302 dataKBs resulted in maximum support value of 1.66%, maximum confidence value of 100%, and maximum lift ratio of 60.24.